2005
DOI: 10.1183/09031936.05.00028305
|View full text |Cite
|
Sign up to set email alerts
|

Budesonide/formoterol maintenance and reliever therapy: an effective asthma treatment option?

Abstract: This 12-month dose-titration study assessed the effectiveness of budesonide/ formoterol for maintenance plus relief with a control group using salmeterol/fluticasone for maintenance plus salbutamol for relief.Adolescents and adults (n52,143; mean forced expiratory volume in one second (FEV1) 73% predicted; mean inhaled corticosteroid (ICS) 884 mg?day ). The simplified strategy using budesonide/formoterol for maintenance and reliever therapy is feasible, safe and at least as effective as salmeterol/fluticasone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
183
4
29

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 193 publications
(226 citation statements)
references
References 32 publications
(41 reference statements)
10
183
4
29
Order By: Relevance
“…More recent work has suggested that when treatment reduction is indicated it is best to reduce the glucocorticoid dose rather than remove the LABA [134]. Currently, overall, there is no clear clinical evidence that suggests that one drug combination is better than the other in the short term [135] although differences in the device may be important in lung deposition in asthmatic patients with poor inspiratory flow [136] and treatment regimes may benefit some patients over others [125,133,137,138]. Indeed, the recent demonstration that the combination of formoterol/beclomethasone in a single inhaler is equivalent to formoterol/budesonide and salmeterol/ fluticasone with respect to asthma control, rates of asthma exacerbations and frequency of adverse events emphasises this point [139][140][141].…”
Section: Moderate Persistent Asthmamentioning
confidence: 99%
“…More recent work has suggested that when treatment reduction is indicated it is best to reduce the glucocorticoid dose rather than remove the LABA [134]. Currently, overall, there is no clear clinical evidence that suggests that one drug combination is better than the other in the short term [135] although differences in the device may be important in lung deposition in asthmatic patients with poor inspiratory flow [136] and treatment regimes may benefit some patients over others [125,133,137,138]. Indeed, the recent demonstration that the combination of formoterol/beclomethasone in a single inhaler is equivalent to formoterol/budesonide and salmeterol/ fluticasone with respect to asthma control, rates of asthma exacerbations and frequency of adverse events emphasises this point [139][140][141].…”
Section: Moderate Persistent Asthmamentioning
confidence: 99%
“…Kuna et al (44) reported similar clinically relevant improvements in overall AQLQ scores (increases of 0.76-0.78) and in scores from each of the AQLQ domains with budesonide/formoterol maintenance and reliever therapy compared with higher fixed doses of ICS/LABA plus SABA. In a dose-titration study conducted by Vogelmeier et al (46) designed to mirror the real-life clinical setting, similar and clinically relevant increases in overall AQLQ score from run-in (0.57-0.60) were reported. Changes in AQLQ were not significantly different between the treatment groups.…”
Section: Improving Daily Asthma Control and Reducing Impairmentmentioning
confidence: 95%
“…Using this definition of asthma control, Buhl and Vogelmeier (49) reported equivalent control with budesonide/formoterol maintenance and reliever therapy compared with fixed-dose ICS/LABA plus SABA. In a dose-titration study, a greater proportion of patients (76% vs 66%) achieved well-controlled asthma with budesonide/ formoterol maintenance and reliever therapy compared with salmeterol/fluticasone plus SABA, and with higher probability of achieving this level of control (odds ratio 1.68; 95% CI 1.38-2.05; P < 0.001) (46). Periods with high reliever use, indicating poorly controlled asthma, are a risk factor for life-threatening asthma (50).…”
Section: Improving Daily Asthma Control and Reducing Impairmentmentioning
confidence: 99%
See 2 more Smart Citations